Four new tri-forked species of the Australian genus Abantiades Herrich-Schäffer (Lepidoptera: Hepialidae) from the “dark obscura clade” - Moore, Michael D.; Beaver, Ethan P.; Velasco-Castrillón, Alejandro; Stevens, Mark I. (Zootaxa, 2020)
A distinct group of Abantiades Herrich-Schäffer species is here confirmed as a valid clade that we refer to as the “dark obscura clade” supported by morphological and mtDNA evidence. The clade is the sister group of A. obscura Simonsen of north-western Australia and comprises four new species: Abantiades centralia sp. nov., A. kayi sp. nov., A. zonatriticum sp. nov., and A. hutchinsoni sp. nov. These species together with A. obscura, are reciprocally allopatric and have a combined distribution spanning much of the western half of Australia and this distribution is consistent with their each differentiating locally from a widespread ancestor. The four new species raise the diversity of Abantiades to 42 species. [Zoobank urn:lsid:zoobank.org:pub:C05458D1-0D34-4432-8EC4-D031ED6B7BEF]